A planar C3Ca2 film: a novel 2p Dirac half metal. Issue 33 (10th August 2017) - Ji, Wei-xiao; Zhang, Bao-min; Zhang, Shu-feng; Zhang, Chang-wen; Ding, Meng; Li, Ping; Wang, Pei-ji
Abstract : A novel planar 2p Dirac half metal C3 Ca2 is presented based on density functional calculation. Abstract : The exploration of Dirac materials is a great challenge in condensed matter physics and material chemistry. In this paper we present a novel 2D magnetic graphene-like Dirac material with a Honeycomb–Kagome (HK) lattice, named as C3 Ca2 . The ground state of C3 Ca2 is a half-metal with a 100% spin polarized Dirac cone locating exactly at the Fermi level in the metallic spin channel, and has a large band gap in the insulating spin channel. In particular, C3 Ca2 has 2p magnetism with the Dirac cones mainly contributed by p xy orbitals of C atoms, instead of 3d magnetism or p z dominated Dirac cones in other HK or Kagome materials, and it is robust against spin–orbit coupling and biaxial strains. The mechanism of magnetism could be understood by double exchange between carbon anions, using Ca 2+ cations as bridges. These outstanding properties of C3 Ca2 indicate it to be a promising 2D material for applications in spintronics.